The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/srep39953
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the enhanced Oxygen Vacancy Formation in Complex Oxides during Annealing and Growth

Abstract: The reduction of oxides during annealing and growth in low pressure processes is a widely known problem. We hence investigate the influence of mere annealing and of growth in vacuum systems to shed light on the reasons behind the reduction of perovskites. When comparing the existing literature regarding the reduction of the perovskite model material SrTiO3 it is conspicuous that one finds different oxygen pressures required to achieve reduction for vacuum annealing and for chemically controlled reducing atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 40 publications
3
39
0
Order By: Relevance
“…[22] An increase of the SrO-termination to 50% results in an increase of the sheet resistance, to about 10 4 Ω at room temperature and about 10 3 Ω below 50 K. This is the typical temperature dependency of the sheet resistance for crystalline LAO/STO dominated by 2DEG conductivity. [11,14,22,[37][38][39][40][41][42][63][64][65] Increasing the SrO-termination further to 100 % did, in agreement with observations reported in literature, [42,43] result in insulating samples, whose sheet resistance is above the measurement limit (10 8 Ω). temperature and STO termination.…”
Section: Application To Lao/sto Heterostructuressupporting
confidence: 85%
See 3 more Smart Citations
“…[22] An increase of the SrO-termination to 50% results in an increase of the sheet resistance, to about 10 4 Ω at room temperature and about 10 3 Ω below 50 K. This is the typical temperature dependency of the sheet resistance for crystalline LAO/STO dominated by 2DEG conductivity. [11,14,22,[37][38][39][40][41][42][63][64][65] Increasing the SrO-termination further to 100 % did, in agreement with observations reported in literature, [42,43] result in insulating samples, whose sheet resistance is above the measurement limit (10 8 Ω). temperature and STO termination.…”
Section: Application To Lao/sto Heterostructuressupporting
confidence: 85%
“…We have previously shown that the growth of crystalline LAO at oxygen pressures ≤ 10 −3 mbar results in a shift from 2DEG conductivity to bulk conductivity, when quenching the sample immediately after growth. [11,22] The appearance of bulk conductivity in crystalline LAO/STO can be explained by the incorporation of oxygen vacancies in the STO bulk, which contribute electrons to the conduction band. During its low pressure growth, LAO sucks oxygen from the underlying STO substrate resulting in the formation of oxygen vacancies in the STO.…”
Section: Application To Lao/sto Heterostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that great care has to be taken when comparing thermal reduction treatments on ternary perovskite‐type titanates performed in different vacuum systems. The local oxygen partial pressure can differ significantly from the expectation not only depending on ionizing measurement devices but also on the materials used in the system, e.g., when Ti or Si is employed as getter material, overlayer or substrate the possibility of incongruent sublimation should be kept in mind. Sublimation effects may also play a role when local reduction at sufficient high temperature is performed by ion beams since O tends to be preferentially sputtered, or by electron irradiation or X‐rays (radiolytic damage).…”
mentioning
confidence: 99%